Studi Tentang Kepemimpinan Kaprodi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah Palembang Dalam Mencapai Visi dan Misi - Rabbul Izzatin; Rabial Kanada (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2018)
Vision and mission are the ultimate goals that serve as guidelines for the activity of study programs and can be used as a basis for the strength of services. However, many study programs only make the vision and mission only available, but do not become meaningful guidelines for the implementation of education. This study aims to describe and analyze the leadership of students in achieving their vision and mission. This study uses a qualitative approach with case studies. Data collection methods used were interviews, field observations, and document studies. The results of the study indicate that leadership is full of openness so that the relationships that are established are very harmonious, harmonious and mutually supportive. The leadership of the study program in an effort to achieve the vision and mission of the study program is carried out by building individual expectations into a shared vision, making development priorities with indicators of achievement, building achievement motivation, increasing participation, and building partnerships with various parties.